Fosterage in medieval Ireland : an emotional history - O'Donnell, Thomas C. (Amsterdam : Amsterdam University Press, 2020)
Fosterage was a central feature of medieval Irish society, yet the widespread practice of sending children to another family to be cared for until they reached adulthood is a surprisingly neglected topic. Where it has been discussed, fosterage is usually conceptualised and treated as a purely legal institution. This work seeks to outline the emotional impact of growing up within another family. What emerges is a complex picture of deeply felt emotional ties binding the foster family together. These emotions are unique to the social practice of fosterage, and we see the language and feelings originating within the foster family being used to describe other relationships such as those in the monastery or between humans and animals. This book argues that the more we understand how people felt in fosterage, the more we understand medieval Ireland.
A permeable boundary between human and animal -- Becoming human -- Through an animal darkly -- Conclusion -- Drawing the chapters together -- Revisiting the methodology -- Bibliography -- Manuscript sources -- Primary sources -- Secondary sources -- About the Author -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 28, 2020).
eBooks on EBSCOhost
Keywords: Foster children -- Ireland -- History -- To 1500.; Foster home care -- Ireland -- History -- To 1500.; Emotions -- Social aspects -- Ireland -- History; British and Irish history; Early history: c. 500 to c. 1450/1500.; Adoption and fostering; HISTORY -- Europe -- Ireland; Emotions -- Social aspects; Foster children; Foster home care; Ireland; To 1500; History of childhood; Irish literature; history of emotions; medieval Ireland; History